Estudo morfológico e histomorfométrico sobre variações sazonais do ducto deferente de codorna da variedade italiana - Viegas, Katia Aparecida da Silva; Orsi, Antonio Marcos [UNESP]; Simões, Karina (My University, 2006)
In the autumn the vas deferens of the Italian variety of domestic quail appeared as a single, thin, and straight duct along its total extension. Thus, transversal histologic sections of this duct showed a circular tubular shape. The pseudoestratified columnar epithelium that lined the vas deferens presented longitudinal folds which invaded the lumen frequently empty of spermatozoa. Although in the winter, spring and summer the usual morphological appearance of the quail's vas deferens was seen as a highly coiling duct. So, each transversal histologic section of the vas deferens, in all the segments, showed parallel cut sections of the duct being irregular in shape and variable in number and interconnected by the adventitial loose connective tissue. In these observations, the tubular lumen was totally performed by spermatozoa and seminal fluid. Consequently, with previous base on the testis kinetics of the Italian quail variety, it was concluded that the spermatozoa production, followed by emission, storage and ejaculation of spermatozoa through the vas deferens did not stop during the winter, spring and summer, but ceased in the autumn the quiescent phase of the circannual reproductive cycle in this bird.
Seasonal study quail's vas deferens of Italian variety: Morphology and histomorphometry
Keywords: Domestic quail; Italian variety; Morphology; Seasonal variability; Vas deferens; Aves; Phasianidae